Income Shifting out of the United States by Foreign Multinational Firms - Albertus, James F (Review of Financial Studies, 2025)
I find that foreign multinational firms engage in tax-motivated income shifting out of the United States. The analysis uses novel data on foreign-owned U.S. subsidiaries as well as variation in foreign countries’ tax rates and controlled foreign corporation rules. Foreign multinational firms primarily rely on tax-motivated transfer pricing to shift income out of the United States, and the aggregate amount of shifted income is modest. When foreign tax policy changes inhibit income shifting, foreign-owned U.S. subsidiaries’ investment and employment fall. The results indicate that the U.S. economy has limited exposure to tax policies set abroad through foreign direct investment in the United States.